Gallbladder cancer and dysplasia in cholecystectomy specimens: a large study in high-incidence regions of South America - Boekstegers, Felix; Barahona Ponce, Carol; Morales, Erik; Muñoz-Castro, Cesar; Lindner, Cristian; Lira, Ivan Schneider; Manques, Belarmino; Flores, Alicia Colombo; Valenzuela, Catalina; Castillo, Jaime; de Toro, Gonzalo; Almau, Mauricio; et al. (Clinical gastroenterology and hepatology, 2025)
Background and Aims - Gallstone disease has been causally linked to gallbladder cancer (GBC) via the carcinogenesis model of gallstones and inflammation leading to gallbladder dysplasia then GBC. Efficient GBC prevention through cholecystectomy requires accurate prediction of individual GBC risk, especially in low- and middle-income regions, where studies tend to be small and of low quality, and where financial and surgical capacity are limited. - Methods - In a collaborative study from high GBC incidence regions of Argentina, Bolivia, Chile, and Peru, we collected and validated clinical information from 10,561 patients with gallstone disease who underwent cholecystectomy. After checking data reliability, we used multiple logistic regression to identify the main factors associated with GBC and dysplasia risk. - Results - The highest GBC and dysplasia risk was found in patients with clinical suspicion of GBC, followed by planned open cholecystectomy, female sex, gallstones over 3 cm, hypercholesterolemia, smoking, and age at cholecystectomy. Clinical suspicion of GBC and age at cholecystectomy showed heterogeneous odds ratios depending on the recruitment site. The identified risk factors, and the magnitude of their effects, were different for GBC and dysplasia. The mean age at cholecystectomy was 47 years, compared with 50 years for low-grade dysplasia, 62 years for high-grade dysplasia, and 64 years for GBC. - Conclusions - These recruitment site-specific risk factors may help refine current prevention strategies by prioritizing prophylactic cholecystectomy in high-risk patients. The approach used in this study may guide future investigations on GBC prevention in high-incidence, low-income regions.
Gesehen am 18.02.2026